Role of Parental Attachment Styles in Moderating Interaction Between Parenting Stress and Perceived Infant Characteristics - Quintigliano, Maria; Trentini, Cristina; Fortunato, Alexandro; Lauriola, Marco; Speranza, Anna Maria (Frontiers in Psychology, 2021)
By employing the transactional model of development and focusing on the multifactorial nature of parenting, this study aimed to (1) examine whether important risk factors, particularly mothers’ insecure attachment styles and parenting stress contribute to the perception of their infants’ characteristics and (2) explore whether maternal attachment styles moderate the relationship between parenting stress and perceived infants’ characteristics. We recruited 357 mothers (age: 34.23; ± 5.38) who had 1-year-old infants (161 males and 196 females; age: 12.70; ± 1.60 months). All the mothers completed three self-report instruments: Parenting Stress Index–Short Form (PSI-SF), Attachment Style Questionnaire (ASQ), and 1st-Year Inventory (FYI). Although the latter was originally developed to determine the risk for autism in 1-year-olds, it was employed in this study to measure infant’s characteristics within two domains: social communication and sensory regulatory functions. Multiple regression analyses revealed that one of the PSI-SF dimensions - specifically the Parent–Child Dysfunctional Interaction - contributed to mothers’ perceptions of their children’s social communication abilities, whereas the attachment style did not. Other multiple regression analyses showed that all the dimensions of parenting stress - that is, Parenting Distress (PD), Parent-Child Dysfunctional Interaction (PCDI), and Difficult Child (DC) - contributed to mothers’ perceptions of their sensory regulatory abilities. The attachment styles, particularly anxious attachment, contributed significantly to a biased perception of these abilities controlled for parenting stress. Mothers reporting high levels of avoidance and high levels of PD viewed their children as less able in the social communicative domain (SC Dom) than if they had low levels of PD. By contrast, when levels of avoidance were low, mothers with high PD perceived their children as less difficult in the SC Dom than those with low levels of PD. Moreover, high avoidance levels influenced how mothers who considered the interaction with their children as difficult perceived them as having greater difficulties in relation to sensory regulatory domain (SR Dom). By contrast, mothers with high levels of anxiety high levels of PD view their children as less able in the SC Dom than if they had low levels of PD. When mothers’ levels of anxiety were very low, those with high PD viewed their children as less difficult in the SC Dom in comparison to those with low levels of PD.